Work measurement - Bollinger, Steven R.; Pardee, Clarke (Manufacturing insights, 2003)
"Explains current practices in work measurement and shows how manufacturers use this procedure to measure productivity improvements." Visits Cooper Instrument Corporation, MacGregor Golf, Cramerton Automotive Products, and Kohler factories to show how they use this procedure. Interviews Royal Dossett and Donovan Young.